2023
DOI: 10.1002/pi.6562
|View full text |Cite
|
Sign up to set email alerts
|

Reaction‐induced morphology control in block copolymers

Abstract: Controlling the self‐assembly behaviors of block copolymers (BCPs) is a focal point of many research thrusts due to their broad use in various applications. While BCP molecular weight, volume fraction, and chemical identities are key thermodynamic parameters to determine their morphology, an emergent method in this area is through reaction‐induced changes to the characteristics of a BCP in situ, which provides access to multiple morphologies and domain sizes from a single parent polymer, as well as enabling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…While the initial study suggested that varying the reaction temperature can have a major impact on the kinetics of the simultaneous sulfonation and cross-linking reactions, a fundamental understanding of the reaction conditions for developing the nanostructure and chemistry of precursors is still very lacking. Understanding the mechanisms associated with the altered nanostructures of SEBS precursors during sulfonation-induced cross-linking is critical for rational system design with direct control over final pore textures by tuning precursor self-assembly behaviors . Here, this work focuses on deconvoluting the effects of simultaneous reactions on the nanostructure development of a SEBS precursor, allowing a more complete understanding of the intricate self-assembly and nanostructural rearrangement process during sulfonation-induced cross-linking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the initial study suggested that varying the reaction temperature can have a major impact on the kinetics of the simultaneous sulfonation and cross-linking reactions, a fundamental understanding of the reaction conditions for developing the nanostructure and chemistry of precursors is still very lacking. Understanding the mechanisms associated with the altered nanostructures of SEBS precursors during sulfonation-induced cross-linking is critical for rational system design with direct control over final pore textures by tuning precursor self-assembly behaviors . Here, this work focuses on deconvoluting the effects of simultaneous reactions on the nanostructure development of a SEBS precursor, allowing a more complete understanding of the intricate self-assembly and nanostructural rearrangement process during sulfonation-induced cross-linking.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the mechanisms associated with the altered nanostructures of SEBS precursors during sulfonation-induced cross-linking is critical for rational system design with direct control over final pore textures by tuning precursor self-assembly behaviors. 41 Here, this work focuses on deconvoluting the effects of simultaneous reactions on the nanostructure development of a SEBS precursor, allowing a more complete understanding of the intricate self-assembly and nanostructural rearrangement process during sulfonationinduced cross-linking. Consequently, these results can provide insights into the controlled synthesis of OMCs from using TPE precursors and, more broadly, elucidate fundamental BCP selfassembly mechanisms under non-equilibrium conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Morphological characterization with smFL techniques is a relevant research area, 254 and expanding these studies to encompass morphological changes within polymer reactions by coupling fluorescence techniques with other characterizations could justify processes relevant to copolymer synthesis. 256 Future studies may also examine self-assembly behaviors for topological complex polymers, such as star and bottlebrush architectures. Current work utilizes methods such as single-molecule magnetic tweezers to study in situ polymerizations of conjugated polymers, but this has not yet been expanded to singlemolecule fluorescence.…”
Section: Discussionmentioning
confidence: 99%